Diseño de pavimento rígido con base en la evaluación por medio de núcleos de la calle Dr. Teodoro Alvarado Oleas - Campos Lliguin, Jonathan Hernán (2024)
The study on pavement cracking identified the causes and development patterns of cracks, allowing the creation of strategies to improve road durability and safety. It will be observed that the exponential increase in loads contributes to the deterioration of the road in its 20-year design period. The rigid pavement wearing course showed a deterioration of 25.5% throughout its useful life. Analysis of vehicular loads on hard pavement indicated that repeated, high intensity loads cause significant deformations. The design was improved by increasing the strength of the concrete and adjusting the thickness of the slab to 20 cm with a 15 cm granular subbase. These improvements are crucial to increasing the durability and functionality of the streets.......